Stereotactic body radiotherapy: a new non-invasive way to conduct pulmonary artery denervation - Liao, Manzhen; Yao, Taoyue; Xie, Yonghui; Kutty, Shelby; Liu, Jinqiao; Peng, Wei; Huang, Ting; Chen, Huaiyang; Fan, Haoqin; Xiao, Zhenghui; Liu, Qiming; Xiao, Yunbin (Frontiers in Medicine, 2025)
BackgroundPulmonary arterial hypertension is a severe and life-threatening disease characterized by a progressive increase in pulmonary vascular resistance. Catheter-based pulmonary artery denervation (PADN) has been conducted in pulmonary arterial hypertension patients; however, if stereotactic body radiotherapy (SBRT) can become a new non-invasive way to conduct, PADN has not been elucidated.MethodsA total of 12 healthy male New Zealand rabbits were digitally marked on their foreheads and randomly divided into the control group (n = 6) and SBRT group (n = 6) at a ratio of 1:1 using computer-generated random numbers. In the SBRT group, rabbits were treated with a single dose of 15 Grey and then bred for a minimum of 3 months. The rabbit models of acute thromboembolic pulmonary arterial hypertension (ATEPAH) were established by injecting autologous blood clots into the femoral vein. Right ventricular function and hemodynamics were assessed by echocardiography and right heart catheterization. Pulmonary artery sympathetic nerves were evaluated by pathological staining.ResultsThe SBRT procedure was successfully performed in all six rabbits. Compared to the control group, SBRT-PADN reduced pulmonary artery systolic pressure and mean pulmonary artery pressure in ATEPAH rabbits. Meanwhile, SBRT-PADN could attenuate pulmonary artery dilatation in ATEPAH rabbits. Histological examination revealed evident structural damages in sympathetic nerves of SBRT-PADN animals, including vacuolization, nuclear pyknosis, and digestion chambers. No adverse events had been observed, and sparing of pulmonary artery of the intima and media was detected up to 90 days post-procedure.ConclusionSBRT could destroy sympathetic nerves around pulmonary artery locally, which may represent a novel option for performing PADN. In addition, this study provided its short-term effectiveness and safety.